2006
DOI: 10.1210/me.2005-0259
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α Interacts with Gα13 to Drive Actin Remodeling and Endothelial Cell Migration via the RhoA/Rho Kinase/Moesin Pathway

Abstract: Sex steroids control cell movement and tissue organization; however, little is known of the involved mechanisms. This report describes the ongoing dynamic regulation by estrogen of the actin cytoskeleton and cell movement in human vascular endothelial cells that depends on rapid activation of the actin-regulatory protein moesin. Moesin activation is triggered by the interaction of the C-terminal portion of cell membrane estrogen receptor alpha with the G protein Galpha(13), leading to activation of the small G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
157
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(170 citation statements)
references
References 44 publications
13
157
0
Order By: Relevance
“…Previously, we and others have demonstrated that estrogen induces vasodilatation, and regulates vascular cell growth and migration as well as protects cardiomyocytes from injury (Simoncini et al 2006, Liu et al 2007, Kublickiene et al 2008. The present study reveals that estrogen exerts anti-inflammatory activity in VSMCs by reducing LPS-induced MCP-1 production, thus inhibiting cell migration.…”
Section: Discussionsupporting
confidence: 69%
“…Previously, we and others have demonstrated that estrogen induces vasodilatation, and regulates vascular cell growth and migration as well as protects cardiomyocytes from injury (Simoncini et al 2006, Liu et al 2007, Kublickiene et al 2008. The present study reveals that estrogen exerts anti-inflammatory activity in VSMCs by reducing LPS-induced MCP-1 production, thus inhibiting cell migration.…”
Section: Discussionsupporting
confidence: 69%
“…The mER and caveolin in myelin partition to a low density detergent-insoluble glycosphingolipid/cholesterol-enriched fraction containing actin and tubulin (Arvanitis et al, 2005). Simoncini et al (2006) revealed a novel nongenomic function of mERa in EC, triggered by its interaction with the G protein Ga 13, resulting in remodeling of the actin cytoskeleton. Remodeling of the cytoskeleton and changes in cell morphology are important events in OL maturation and myelination processes.…”
Section: Discussionmentioning
confidence: 96%
“…Simoncini T et al [16] have detected the expression of NHERF1 in HUVECs and speculated that it might play a certain role in angiogenesis. Song GJ et al [17] found that NHERF1 is only expressed in normal vascular endothelial cells, but almost not in vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%